40 Years Old Mass, Resting in Male Breast; A Rare Epidermal Inclusion Cyst - Muhammad Danish Muneeb; Mirza Aga Naushad Baig; Khalid Ahmed Ahmed (Journal of the Dow University of Health Sciences, 2021)
We present a case of 50-years-old male, with right breastepidermoid cyst,whose enlargement over the past few months caught the attention, due to its harmless nature its enlargement since 40 years was ignored by patient. Its occurrence in the breast tissue is rare as documented in literature. However, clinicians might find difficulty in differentiating it from other breast swellings like gynecomastia, fibroadenoma, or benign and malignant conditions of breast. The purpose of this case report is to increase the awareness among the general surgeons of this rare presentation; and to entertain the phenomenon of diagnosing with simple radiological modalities.Complete excision using elliptical incision is still the surgical treatment of choice.